The intersection of self and social identity in heritage brand destination - Norfardilawati Musa; Shuhaida Md Noor (Penerbit Universiti Kebangsaan Malaysia, 2020)
The recognition from the United Nations Educational, Scientific and Cultural Organisation (UNESCO) on heritage tourism draws destination tourists both international and local. Lenggong Valley (LV) is well-known with the Perak Man and archaeological sites. Since its discovery and inscription as one of the UNESCO world heritage sites in 2012, relevant planning has been established to develop the area as part of tourism destinations in Malaysia. Developing a brand destination is intricate in view of its multifaceted structure and multiple stakeholders with different interests that a destination possessed. The early stage for the identification of destination-brand identity is crucial in ensuring the involvement of its stakeholders, particularly the residents. The key reason offered by most of the literature reviews for destination branding is, this group plays an important role in providing destination experiences to the tourists. The focus of this research is to give an overview and discuss how the self and social identity that underlie the resident’s evaluation are intersected, which affects their interpretation of destination-brand identity. Adopting a qualitative method and guided by the stakeholder and social identity theories, the data collection was conducted in two phases – (i) in-depth interviews; and (ii) focus group interview (FGI). The participants were purposively selected consisting of the headmen and some representatives of the female residents to represent the residents’ perspectives. Data were analysed using the 6-step thematic analysis. The findings revealed that residents’ conceptualization of the Lenggong Valley World Heritage Site’s identity revolves around the intersection between their self and social identities.